TINGKAT PENGETAHUAN IBU TENTANG PIJAT BAYI TERHDAP PERKEMBANGAN MOTORIK ANAK DI PMB SUPADMI IRIANTO BULU SUKOHARJO - nawes; Supadmi (Sekolah Tinggi Ilmu Kesehatan Mitra Husada Karanganyar, 2025)
Massage is a good, useful and healthy therapy for your baby. Apart from strengthening the bond between parent and child, baby massage also helps the child's growth and development to be better. Baby massage is also an expression of affection between parents and children through touching the skin which can have a tremendous impact on physical, emotional and growth development. Baby massage is also interpreted as a therapy that has been carried out by parents in the past and is popular as an art of care. Currently, baby massage is starting to be developed, for which a lot of research has been carried out. Baby massage is also a type of stimulation that can be done on babies to stimulate various developments that babies must go through, including motor development. Method The type of research used is descriptive quantitative with a cross sectional design. The research was conducted at PMB Supadmi Irianto in January 2025. The sample used in this research was 30 respondents. The sample size was determined using accidental sampling technique.